Leveraging Learners’ Metacognitive Activities for Recommendation in Technology Enhanced Learning Systems - Odilinye , Lydia; Popowich , Fred (Journal of Organizational Psychology, 2021)
There has been a growing interest in assisting learners develop control over their learning and behaviour. Metacognition — the ability to think about thinking — can be an effective learning strategy that encourages learners take control of their learning. Typically, while reading, learners engage in a number of metacognitive reading activities e.g. text marking, highlighting. This study examines the effectiveness of utilizing the metacognitive activities generated by learners as a preference elicitation method to guide the recommendation of personalized learning resources. Providing appropriate resources that facilitate personalized learning is considered imperative given that learning differs from one learner to another.